From fb9ecf0b36aa62221f44fc48aaf4363f1c8b752b Mon Sep 17 00:00:00 2001 From: Mitchell Date: Wed, 22 Apr 2020 21:55:49 +1000 Subject: [PATCH] Don't substitute ARIMA equations with non-utf8 characters --- R/arima.R | 6 +++--- man/ARIMA.Rd | 7 +++---- 2 files changed, 6 insertions(+), 7 deletions(-) diff --git a/R/arima.R b/R/arima.R index 5c0efebf..01b275df 100644 --- a/R/arima.R +++ b/R/arima.R @@ -466,13 +466,13 @@ specials_arima <- new_specials( #' #' In fable, the parameterisation used is: #' -#' \deqn{(1-\phi_1B - \cdots - \phi_p B^p)(1-B)^d y_t = c + (1 + \theta_1 B + \cdots + \theta_q B^q)\varepsilon_t}{(1-φ₁B - ⋯ - φₚ Bᵖ)(1-B)ᵈ yₜ = c + (1 + θ₁ B + ⋯ + θ_q B^q)εₜ} +#' \deqn{(1-\phi_1B - \cdots - \phi_p B^p)(1-B)^d y_t = c + (1 + \theta_1 B + \cdots + \theta_q B^q)\varepsilon_t} #' #' In stats and forecast, an ARIMA model is parameterised as: #' -#' \deqn{(1-\phi_1B - \cdots - \phi_p B^p)(y_t' - \mu) = (1 + \theta_1 B + \cdots + \theta_q B^q)\varepsilon_t}{(1-φ₁B - ⋯ - φₚ Bᵖ)(1-B)ᵈ (yₜ - μ tᵈ/d!) = (1 + θ₁ B + ⋯ + θ_q B^q)εₜ} +#' \deqn{(1-\phi_1B - \cdots - \phi_p B^p)(y_t' - \mu) = (1 + \theta_1 B + \cdots + \theta_q B^q)\varepsilon_t} #' -#' where \eqn{\mu} is the mean of \eqn{(1-B)^d y_t}{(1-B)ᵈ yₜ} and \eqn{c = \mu(1-\phi_1 - \cdots - \phi_p )}{c = μ(1-φ₁ - ⋯ - φₚ )}. +#' where \eqn{\mu} is the mean of \eqn{(1-B)^d y_t} and \eqn{c = \mu(1-\phi_1 - \cdots - \phi_p )}. #' #' @section Specials: #' diff --git a/man/ARIMA.Rd b/man/ARIMA.Rd index 8504f820..1db54b12 100644 --- a/man/ARIMA.Rd +++ b/man/ARIMA.Rd @@ -53,14 +53,13 @@ are equivalent, the coefficients for the constant/mean will differ. In fable, the parameterisation used is: -\deqn{(1-\phi_1B - \cdots - \phi_p B^p)(1-B)^d y_t = c + (1 + \theta_1 B + \cdots + \theta_q B^q)\varepsilon_t}{(1-φ₁B - ⋯ - φₚ Bᵖ)(1-B)ᵈ yₜ = c + (1 + θ₁ B + ⋯ + θ_q B^q)εₜ} +\deqn{(1-\phi_1B - \cdots - \phi_p B^p)(1-B)^d y_t = c + (1 + \theta_1 B + \cdots + \theta_q B^q)\varepsilon_t} In stats and forecast, an ARIMA model is parameterised as: -\deqn{(1-\phi_1B - \cdots - \phi_p B^p)(y_t' - \mu) = (1 + \theta_1 B + \cdots + \theta_q B^q)\varepsilon_t}{(1-φ₁B - ⋯ - φₚ Bᵖ)(1-B)ᵈ (yₜ - μ tᵈ/d!) = (1 + θ₁ B + ⋯ + θ_q B^q)εₜ} - -where \eqn{\mu} is the mean of \eqn{(1-B)^d y_t}{(1-B)ᵈ yₜ} and \eqn{c = \mu(1-\phi_1 - \cdots - \phi_p )}{c = μ(1-φ₁ - ⋯ - φₚ )}. +\deqn{(1-\phi_1B - \cdots - \phi_p B^p)(y_t' - \mu) = (1 + \theta_1 B + \cdots + \theta_q B^q)\varepsilon_t} +where \eqn{\mu} is the mean of \eqn{(1-B)^d y_t} and \eqn{c = \mu(1-\phi_1 - \cdots - \phi_p )}. } \section{Specials}{